Interchange 1 : video - Dean, Christina A. (Master Communications Group, 1999)
Sumario: Video con temas cortos de apoyo en la enseñanza del inglés conversacional. Abarca temas como: Greetings, Works and jobs, Garage sale, Movies, To stay in shape, Travel, Kinds of music, etc.